Peran Lingkungan Kerja, Disiplin Kerja, dan Motivasi Kerja pada Kinerja Karyawan PT. Pesona Arnos Beton Gresik - Arianto, Bisma; Fathorrahman; Vina Puspita Ningrum (Universitas PGRI Adi Buana, 2025)
This study aims to analyze the influence of work environment, work discipline, and work motivation on employee performance at PT. Pesona Arnos Beton Gresik. All 72 employees were used as respondents in this study using the saturated sampling method. The data collection process was carried out by distributing closed questionnaires that had been systematically designed to measure respondents' perceptions of each research variable. The instrument was compiled based on indicators that were relevant to the dimensions of the work environment, work discipline, motivation, and employee performance, so that valid and reliable data could be obtained for quantitative analysis. Data analysis using SPSS version 23 software. The statistical results showed that the three independent variables, namely the work environment, work discipline, and work motivation, each individually had a positive and significant influence on employee performance. A supportive work environment, high discipline, and strong work motivation contributed significantly to improving employee performance at PT. Pesona Arnos Beton Gresik. These findings can be used as a basis for initial consideration for management in formulating a more focused and effective human resource development strategy, by referring to empirical evidence obtained through research.